Artificial extrusion of spermatophores for insemination of the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa; Gur, Seyfettin (Elsevier, 2019)
The extrusion of spermatophores using electrical stimulation and dissection techniques from the vas deference was performed to test the feasibility of artificial insemination in Pontastacus leptodactylus. The electrical stimulation to males showed a significant success of 66.6%. The rate of spermatophore ejaculation was affected by male size (P < 0.05). Higher number of spermatophores and percentage of spermatophore ejaculation were observed in large (> 6.5cm carapace length) males (1.4 +/- 0.1; 92.3%) compared to medium (5.5-6.5 cm carapace length) (1.1 +/- 0.1; 75%) and small (< 5.5 cm carapace length) males (0.6 +/- 0.2; 33.3%). It was found that the extrusion technique did not affect spermatozoa viability (P > 0.05). Viability was 80.4 +/- 2.2% and 83.8 +/- 1.9% for electrical stimulation and dissection techniques, respectively. The spawning rate was 100% in inseminated females using spermatophores obtained from the dissected males. Using electrical extrusion, not enough spermatozoa were obtained to induce spawning in female P. leptodactylus. Further studies are needed to improve the outcome of the electrical extrusion technique. The present study represents a step forward for the development of artificial insemination in P. leptodactylus.
Keywords: Decapod; Electrical stimulation; Fertilization; Spawning; Sperm